Factors that differentiate acceleration ability in field sport athletes - Lockie, R. G.; Murphy, A. J.; Knight, T. J.; Janse de Jonge, X. A. K. (The Journal of Strength and Conditioning Research, 2011)
Speed and acceleration are essential for field sport athletes. However, the mechanical factors important for field sport acceleration have not been established in the scientific literature. The purpose of this study was to determine the biomechanical and performance factors that differentiate sprint acceleration ability in field sport athletes. Twenty men completed sprint tests for biomechanical analysis and tests of power, strength, and leg stiffness. The sprint intervals analyzed were 0-5, 5-10, and 0-10 m. The subjects were split into a faster and slower group based on 0- to 10-m velocity. A 1-way analysis of variance determined variables that significantly (p <= 0.05) distinguished between faster and slower acceleration. All subject data were then pooled for a correlation analysis to determine factors contributing most to acceleration. The results showed that 0- to 5-m (~16% difference) and 0- to 10-m (~11% difference) contact times for the faster group were significantly lower. Times to peak vertical and horizontal force during ground contact were lower for the faster group. This was associated with the reduced support times achieved by faster accelerators and their ability to generate force quickly. Ground contact force profiles during initial acceleration are useful discriminators of sprint performance in field sport athletes. For the strength and power measures, the faster group demonstrated a 14% greater countermovement jump and 48% greater reactive strength index. Significant correlations were found between velocity (0-5, 5-10, and 0-10 m) and most strength and power measures. The novel finding of this study is that training programs directed toward improving field sport sprint acceleration should aim to reduce contact time and improve ground force efficiency. It is important that even during the short sprints required for field sports, practitioners focus on good technique with short contact times.